On-line preconcentration/determination of lead traces in bee honey by inductively coupled plasma optical emission spectrometry (ICP-OES) using a conical minicolumn packed with activated carbon - Cerutti, Estela Soledad (2003)
In this study, the preconcentration of Pb2+ using a conical minicolumn packed with activated carbon (AC) was studied for preconcentration of Pb2+. The experiments showed that Pb2+ reacts with 8-hydroxyquinoline to form a complex at pH 10.0 and can be retained "on-line" on a conical minicolumn packed with activated carbon, then eluted with 20% (v/v) nitric acid. The conditions for the quantitative and reproducible preconcentration and subsequent ICP-OES determination with ultrasonic nebulization system (USN) were studied. A total enhancement factor (N) of 500 was obtained with respect to ICP-OES using pneumatic nebulization (10 for USN and 50 for enrichment factor) for a sample volume of 25 mL. The detection limit (DL) was 0.04 μg L-1. The relative standard deviation (RSD) were 3.0%. The optimized procedure was successfully applied to the determination of trace levels of Pb+2 in bee honey samples.